Spatiotemporal analysis of rabies in South Africa, the role of black-backed jackals (Canis mesomelas) and aspects of its control by oral rabies vaccination - Thompson, P.N. (Peter N.) (University of Pretoria, 2022)
Thesis (PhD)--University of Pretoria, 2020.